Essential values of cocaine and non‐drug alternatives predict the choice between them. (14th September 2016) - Kearns, David N.; Kim, Jung S.; Tunstall, Brendan J.; Silberberg, Alan
Abstract: This study investigated the relationship between reinforcer value and choice between cocaine and two non‐drug alternative reinforcers in rats. The essential value (EV, a behavioral economic measure based on elasticity of demand) of intravenous cocaine and food (Experiment 1) or saccharin (Experiment 2) was determined in the first phase of each experiment. Food had higher EV than cocaine, whereas the EVs of cocaine and saccharin did not differ. In the second phase of each experiment, rats were allowed to make mutually exclusive choices between cocaine and the non‐drug alternative reinforcer. The main findings were that the EV of cocaine was a positive predictor of cocaine preference and the EV of food or saccharin was a negative predictor of cocaine preference. An analysis of within‐session patterns of choice behavior revealed sequential dependencies, whereby rats were more likely to choose cocaine on a particular trial after having chosen the non‐drug alternative on previous trials. When the time between choices was increased, these sequential dependencies disappeared. The results of these experiments are consistent with the suggestion that addiction‐like behavior involves both overvaluation of drug reinforcers and undervaluation of non‐drug reinforcers. Abstract : Individual differences in how rats valued cocaine or a non‐drug alternative (food or saccharin) predicted subsequent choice behavior in an animal model of addiction. Rats that placed either high value on cocaine or low value on the non‐drug alternative were most likely to prefer cocaine. These results are consistent with the notion that addiction involves both overvaluation of drug rewards and undervaluation of non‐drug alternatives.